(untitled) (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
With the growing reach and adoption of renewable energy, the grid impedance rises significantly, resulting in weak and extremely weak grid conditions that seriously threaten grid stability. Consequently, grid-forming inverters, capable of providing voltage and frequency support, have garnered widespread attention. However, under weak grid conditions, Delays from digital control alters the output impedance performance grid-forming inverters to exhibit negative damping characteristics. Resonance problems at mid and high frequencies arise from the coupling between this output impedance and grid impedance. To address this problem, this paper introduces the passivity theory from the perspective of inverter output impedance and proposes an impedance reshaping strategy based on grid voltage feedforward, transforming the inverter output impedance from active to passive. First, an impedance model of the grid forming inverter is established to analyze the mechanism of resonance generation, and the non-passive characteristics of the output impedance are verified based on passivity theory. Second, through an analysis of the inverter impedance, a novel voltage feedforward function is derived and designed.By appropriately configuring the feedforward parameters, Satisfying passivity conditions at all frequencies, the inverter output impedance achieves resonance suppression. Ultimately, a 10 kW inverter prototype verifies the accuracy of theoretical derivations and the feasibility of the presented control schem.